The hacker: he may be a white hat, a black hat, a phreaker or a script kiddie. But is he just a vandal, or is he a modern-day hero? - Adams, Richard (New Statesman, 2000)
Hackers, who usually get the blame when computers run into problems, come in many forms. This community can be broadly divided into “white hat” and “black hat” users. The white hats are motivated by the challenge competing against the professionals and may even benefit companies by passing their findings on. Black hats are more malicious in breaking into computers. They tamper illegally with computers and pass on their findings to other black hats. Then there is the “phreaker” who specializes in deciphering telephone networks normally to access free calls. However, recently, the hacking scene has been invaded by “script kiddies,” aspiring hackers who use the hacking programs distributed over the Internet by black hats, unleashing most of the petty vandalism on the Internet. The problem lies in the fact that the Internet was designed for access not security, and rather than getting operators to tighten up their systems, the British government chooses to focus on the threat from hackers.